Aging properties of HMB15 with varying binder film thicknesses - Wu, Jiantao; Nur Izzi Md. Yusoff,; Chen, Jun; Liu, Yun; Gordon D. Airey, (Universiti Kebangsaan Malaysia, 2012)
In order to cope with the ever-increasing traffic loading and to minimise the cost of road construction and maintenance, several road trials of high modulus base (HMB) materials containing a 15 penetration grade bitumen (known as HMB15) have been carried out in the UK since 1990s. It has been showed that, although HMB15 behaved in a similar way to conventional dense bitumen Macadam with a cost saving of approximately 25%, its long-term durability (aging and moisture damage) is still a major concern of researchers as considerable deteriorations have been commonly observed during the ongoing investigations on cored samples from the sites (either with or without traffic loading). The aim of this paper was to quantitatively show the relationship between aging properties of HMB15 and its binder film thickness (binder content), so that an optimum binder content could be determined. In order to achieve this, 5 groups of cylindrical HMB15 specimens with different binder contents (3.5%, 4%, 4.5%, 5% and 5.5%) were fabricated and subjected to SHRP long-term oven aging test (at 85oC for 5 days), their mechanical properties both before and after aging simulation were tested using indirect tensile stiffness modulus (ITSM) tests. In addition, binders were recovered at different aging stages and their rheological characteristics were investigated with dynamic shear rheometer (DSR) tests. Based on these, aging indices of different groups were calculated and their mathematical relationship with binder film thicknesses was regressed. The results showed that the aging properties of HMB15 mixtures were significantly affected by their binder film thicknesses. However, regression analysis between aging indices and binder film thicknesses indicated that, as the binder film becomes thicker than 9.5 μm, the change of aging indices with film thicknesses becomes minor and therefore, a film thickness of approximately 9.5 μm was recommended for HMB15 mixtures.